Design of ultra-high temperature ceramic nano-composites from multi-scale length microstructure approach. (1st December 2021) - Gilli, Nicola; Watts, Jeremy; Fahrenholtz, William G.; Sciti, Diletta; Silvestroni, Laura
Abstract: The evolution of the multi-scale microstructure of a (Zr, Ta)B2 solid solution was studied as a function of time and temperature. The ceramics were produced by hot pressing a mixture of ZrB2 with 15 vol% TaSi2 followed by annealing at 2100 °C. Formation of a super-saturated solid solution led to the precipitation of TaC nano-needles within the micron-sized boride grain matrix. Phase stability diagrams were used to define the conditions of partial pressure within the sintering chamber that drove precipitation of nano-inclusions in the form of either metal or carbide. Through this approach, other systems containing various transition metals were explored to design other formulations for in-situ nano-composites with unprecedented strength at ultra-elevated temperatures. Graphical abstract: Image 1